CUSTOMER SATISFACTION AND LOYALTY OF CELLULAR PHONE SUBSCRIBERS IN YOGYAKARTA - , AGATHA BINAR MISARESTI, Benardinus Maria Purweanto, Dr., MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Telecommunication industry is growing and simultaneously become a big source of economic growth, especially in cellular phone industry. People become more mobile and some of them may think that a mobile phone is more important even at home than a fix line phone, which usually installed in houses. This research conducted to examine whether the price setting, the networck coverage, the quality of the signal, the customer service, and the ease of use of the cellular phone provider affect the customer satisfaction